2020
DOI: 10.1038/s41586-020-1973-x
|View full text |Cite
|
Sign up to set email alerts
|

AQP5 enriches for stem cells and cancer origins in the distal stomach

Abstract: This is a repository copy of AQP5 enriches for stem cells and cancer origins in the distal stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 45 publications
(34 reference statements)
8
97
0
Order By: Relevance
“…Consistent with this, Reg KO mice shows significantly decelerated growth and migration of intestinal epithelial cells towards the villus tip (29). Indeed, several Reg family genes are expressed in the endogenous gastric stem cell compartment (Supplementary Figure 8a, b) (4,30). Whilst administration of REGs cannot fully compensate for Wnt withdrawal, Reg genes clearly supported organoid growth.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with this, Reg KO mice shows significantly decelerated growth and migration of intestinal epithelial cells towards the villus tip (29). Indeed, several Reg family genes are expressed in the endogenous gastric stem cell compartment (Supplementary Figure 8a, b) (4,30). Whilst administration of REGs cannot fully compensate for Wnt withdrawal, Reg genes clearly supported organoid growth.…”
Section: Discussionsupporting
confidence: 64%
“…It has been shown that for many gene set analysis methods, whether competitive or self-contained, the results of the analysis are not reproducible for small sample sizes (Maleki et al, 2019a ). However, regardless of this issue, studies with small sample sizes ( n < 5 per group) continue to be analyzed using these methods (Dumesic et al, 2019 ; Weinberg et al, 2019 ; Tan et al, 2020 ). Therefore, it should be stressed that the size of a dataset is an important consideration when deciding on an appropriate gene set analysis method or whether it is appropriate to use gene set analysis at all.…”
Section: Challengesmentioning
confidence: 99%
“…Cholecystokinin type-B receptor (CCK2R)-positive cells are another set of stem cells which does not overlap with Lgr5 + cell population at the antral gastric units, and treatment with progastrin interconverts CCKR2 + Lgr5 neg or low antral stem cells into typical antral Lgr5 high cells that expand the active stem cells in the antrum (Hayakawa et al, 2015b). More recently, AQP5 expressing populations are identified to overlap with Lgr5 + stem cells at the base of pyloric gland, where this population of stems cells comprises the pyloric lineages expressing Muc5AC, gastric intrinsic factor, gastrin and chromogranin A (Tan et al, 2020).…”
Section: Gastric Stem Cell Marker Candidatesmentioning
confidence: 99%
“…Besides Lgr5 + cells, Klf-4 (Kruppel-like factor 4) disruption or PPARD (peroxisome proliferator-activated receptor delta) overexpression in Villin promoter-expressing stem cells spontaneously result in gastric carcinogenesis (Li et al, 2012;Zuo et al, 2019), CCK2R + cells potentially explains the gastrin-mediated effects on gastric cancer progression (Hayakawa et al, 2015b). More recently, AQP5 + stem cells are identified as a source of Wnt-driven gastric cancer, and AQP5 + tumor cells could reproducibly generate organoids in the absence of exogenous growth factors, indicating the stem potential of this cell populations (Tan et al, 2020). For gastric cancer occurred in the corpus, Mist1 + isthmus stem cells can serve as an origin.…”
Section: Gastric Carcinogenesismentioning
confidence: 99%